Legal Responsibility of Social Media Platforms in Addressing Illegal Content in Indonesia - Chairus Suryati (Outline Journal of Community Development, 2023)
In the digital era marked by the rapid development of social media, the spread of illegal content such as hoaxes, hate speech, pornography, fraud, and radicalism has become a serious challenge for society and the government. Social media platforms as digital service providers have a legal responsibility to moderate such content in accordance with applicable legal provisions. This Community Service (PKM) activity aims to increase public understanding, especially the younger generation, regarding the legal aspects that regulate the responsibility of digital platforms in dealing with illegal content, as well as to encourage critical awareness of the importance of a safe and responsible digital space. The methods used in this activity include counseling, group discussions, distributing questionnaires, and post-tests. The results of the activity showed a significant increase in participants' understanding of the types of illegal content and the legal responsibilities of digital platforms. Most participants agreed that platforms should be responsible for problematic content, and considered that the current reporting mechanism was still ineffective. Survey data also showed that hoaxes and fraud were the two types of illegal content most often found. This activity concluded that digital legal education is a strategic step in strengthening public literacy regarding rights and obligations in cyberspace. Collaboration is needed between the community, government, and platform providers to create a digital ecosystem that is healthy, transparent, and in accordance with legal principles in Indonesia.